A multiwavelength study of the ring nebula SG 13 - Vasquez, Javier (2009)
We investigate the morphology and kinematics of the interstellar medium in the environs of the open cluster Mrk 50, which includes the Wolf–Rayet star WR 157 and a number of early B-type stars. The analysis was performed using radio continuum images at 408 and 1420 MHz, and H I 21-cm line data taken from the Canadian Galactic Plane Survey, molecular observations of the 12CO (J= 1 → 0) line at 115 GHz from the Five College Radio Astronomy Observatory and available mid- and far-infrared (FIR) observations obtained with the Midcourse Space Experiment and IRAS satellites, respectively. This study allowed the identification of the radio continuum and molecular counterpart of the ring nebula SG 13, while no neutral atomic structure was found to be associated. The nebula is also detected in the images in the mid- and FIR, showing the existence of dust well mixed with the ionized gas. We estimate the main physical parameters of the material linked to the nebula. The interstellar gas distribution in the environs of Mrk 50 is compatible with a stellar wind bubble created by the mass loss from WR 157. The distribution of young stellar object candidates in the region shows that the stellar formation activity may be present in the molecular shell that encircles the ring nebula.